2020
DOI: 10.1038/s41467-020-18528-z
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing anti-inflammasome NRTIs for improving insulin sensitivity and reducing type 2 diabetes development

Abstract: Innate immune signaling through the NLRP3 inflammasome is activated by multiple diabetes-related stressors, but whether targeting the inflammasome is beneficial for diabetes is still unclear. Nucleoside reverse-transcriptase inhibitors (NRTI), drugs approved to treat HIV-1 and hepatitis B infections, also block inflammasome activation. Here, we show, by analyzing five health insurance databases, that the adjusted risk of incident diabetes is 33% lower in patients with NRTI exposure among 128,861 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 89 publications
4
24
0
Order By: Relevance
“…Randomized controlled trials can yield better causal insights. Recently, we demonstrated NRTI use is associated with reduced development of type 2 diabetes (58). The current findings provide a rationale for prospective testing of NRTIs or alkylated NRTI derivatives, which block inflammasome activation but are less toxic than NRTIs (11), as potential therapies for geographic atrophy as well.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Randomized controlled trials can yield better causal insights. Recently, we demonstrated NRTI use is associated with reduced development of type 2 diabetes (58). The current findings provide a rationale for prospective testing of NRTIs or alkylated NRTI derivatives, which block inflammasome activation but are less toxic than NRTIs (11), as potential therapies for geographic atrophy as well.…”
Section: Discussionmentioning
confidence: 64%
“…First, a large amount of the variance across studies is attributable to heterogeneity (I 2 = 83.1%; 95% CI, 49.3-98.6%; P < 0.001, test A-C) Using methodology employed in ref. 58, aHRs estimated separately for each database shown in black along with their 95% CIs, along with fixed-effect and random-effects meta-analyses shown in diamonds. The dashed vertical line denotes a HR of 1.0, which represents no difference in risk between nucleoside reverse-transcriptase inhibitor (NRTI) exposure and nonexposure.…”
Section: Resultsmentioning
confidence: 99%
“…The role of chronic inflammation in the development of T2D has been well documented, 109 111 and the NLRP3 inflammasome was shown to mediate obesity-induced inflammation and insulin resistance. 112 , 113 A number of molecules such as high glucose, islet amyloid polypeptide, saturated fatty acids, and mitochondrial ROS are involved in activating the NLRP3 inflammasome and contribute to the pathogenesis of T2D.…”
Section: Roles Of Inflammasomes In Sterile Inflammatory Diseasesmentioning
confidence: 99%
“…Moreover, the Prospective Urban Rural Epidemiological study showed that high consumption of white rice can result in an increased risk for incident diabetes (Hu et al, 2012 ; Bhavadharini and Mohan, 2020 ). Moreover, the result of a recent study that nucleotide reverse transcriptase inhibitors can improve insulin sensitivity and reduce the development of type 2 diabetes supports the relationship between the development of type II diabetes mellitus and CNVs extension as well (Ambati et al, 2020 ).…”
Section: Associations With Other Diseasesmentioning
confidence: 73%